Class Management Design For Condusive And Exciting Learning - Sukhron Ependi Harahap; Jangky Dausat; Niza Fadila (Proceeding International Seminar of Islamic Studies, 2019)
One key supporting factor for the achievement of learning objectives is good classroom management. Good management will certainly lead to conducive and fun learning. But to create class conditions like that do not necessarily we can do easily when we want to teach, there are steps that must be done before teaching in determining how the desired class pattern. This paper aims to analyze: (1) Things that can deliver the achievement of learning outcomes, (2) Design patterns of classroom management that are conducive and fun (3) the effectiveness of these patterns in achieving learning success. This study uses qualitative research methods using a descriptive analysis approach. Data collection techniques are done by observation, interviews, and study documentation. This research was conducted at MIS Ubudiyah Medan, for 2 months, and with a total of 7 informants. The results showed that: (1) Several things that deliver the achievement of learning success are good learning planning, good implementation, and measurable evaluation, (2) In managing the different classes of teachers there are patterns that use student ability levels, there are who use the type and characteristics of learning, there are also those who use group class patterns, (3) these patterns have indeed been designed by the teacher and after analysis can indeed achieve student learning success when compared to before not doing classroom management design.